Southern Harmony: Catholic-Protestant Relations in the Antebellum South - Stern, Andrew H. M. (Religion and American culture, 2007)
This essay seeks to recover the experiences of Catholics in the antebellum South by focusing on their relations with Protestants. It argues that, despite incidents of animosity, many southern Protestants accepted and supported Catholics, and Catholics integrated themselves into southern society while maintaining their distinct religious identity. Catholic-Protestant cooperation was most clear in the public spaces the two groups shared. Protestants funded Catholic churches, schools, and hospitals, while Catholics also contributed to Protestant causes. Beyond financial support, each group participated in the institutions created by the other. Catholics and Protestants worshipped in each other's churches, studied in each other's schools, and recovered or died in each other's hospitals. This essay explores a series of hypotheses for the cooperation. It argues that Protestants valued Catholic contributions to southern society; it contends that effective Catholic leaders demonstrated the compatibility of Catholicism and American ideals and institutions; and it examines Catholic attitudes towards slavery as a ground for religious harmony. Catholics proved themselves to be useful citizens, true Americans, and loyal Southerners, and their Protestant neighbors approvingly took note. Catholic-Protestant cooperation complicates the dominant historiographical view of interreligious animosity and offers a model of religious pluralism in an unexpected place and time.